Strategy for Implementing the Teaching Style of Physical Education Teachers for Mentally Disabled Students (Case Study of 2 Special Needs Schools in Kupang City ) - Veramyta Maria Martha Flora Babang; Maria A. Barek Ladjar; Lukas Maria Boleng; Ratno Susanto; Yusuf Nikodomus Lopo (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objectives . To investigate the implementation of the teaching methodology employed by PJOK educators at SLBN Kota Raja and SLB Asuhan Kasih. This research employs a quantitative descriptive methodology via a survey approach. Materials and Methods. Physical education programs for students with disabilities must align with the specific characteristics of these individuals. Educators should possess comprehensive knowledge of the developmental changes experienced by these students to effectively devise strategies and teaching methodologies tailored for children with special needs. Adaptive physical education refers to physical education that has been tailored to accommodate the requirements of children with impairments. The study employed descriptive research using a qualitative methodology. This research engaged physical education instructors in health and sports at SLBN Kota Raja and SLB Asuhan Kasih as participants. Tools used for observation and interviews. Descriptive research seeks to delineate the characteristics of the phenomenon or variable under investigation. This research aims to elucidate the mechanisms or applications of a phenomenon within a specific environment, without attempting to alter or manipulate existing variables. Results. The primary objective of this study is to ascertain the strategy for executing the teaching methodology of PJOK educators for students with disabilities in two special schools in Kupang City, specifically SLB Asuhan Kasih and SLB Kota Raja. This study primarily aims to examine how PJOK teachers modify their instructional approaches to accommodate the unique requirements of students with disabilities and to assess the efficacy of the teaching tactics employed in potentially challenging learning environments. To attain this objective, the most appropriate and pertinent methodology in this study is conducting interviews with PJOK teachers and observing the learning process. Interviews with PJOK educators at SLB Asuhan Kasih and SLB Kota Raja aim to obtain comprehensive understanding of their instructional methodologies. Conclusion. Adaptable Teaching Methodology: PJOK educators in both SLBs employ an adaptable methodology for instructing students with impairments in PJOK. They create resources tailored to students' capabilities and employ diverse pedagogical approaches to address the unique requirements of each learner.